2023
DOI: 10.9734/ijecc/2023/v13i103132
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Studies in Advanced Sugarcane Mid-Late Clones through Yield and Quality Traits

G. Rakesh,
G. Eswara Reddy,
A. Dinesh
et al.

Abstract: Sugarcane varietal development is frequently aimed at increasing yield and sucrose quality. Effective crop genetic evolution requires knowledge of the numerous traits that contribute to the present diversity by genetic analysis. Keeping in view, this experiment was conducted using a randomized block design with three replications and the trial consisted of nine mid-late sugarcane genotypes. Data on cane yield and quality traits were used to estimate the genetic variability parameters, heritability, and genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…They also indicated that single cane weight and number of millable canes were the major contributors to cane yield. These results were further confirmed by Rakesh et al (2023) [15] , Tolera et al (2024) [20] and Sharma et al (2023) [17] by studying path analysis in different sugarcane clones. The combined results of correlation and path coefficient analysis in the present investigation may help to develop suitable selection criteria particularly for this subtropical ecology.…”
Section: Resultssupporting
confidence: 67%
“…They also indicated that single cane weight and number of millable canes were the major contributors to cane yield. These results were further confirmed by Rakesh et al (2023) [15] , Tolera et al (2024) [20] and Sharma et al (2023) [17] by studying path analysis in different sugarcane clones. The combined results of correlation and path coefficient analysis in the present investigation may help to develop suitable selection criteria particularly for this subtropical ecology.…”
Section: Resultssupporting
confidence: 67%